Okay, here we have this:
We need to solve the following system:
x+y+2z=-7 (1)
-5z=25 (2)
3x-3y-6z=3 (3)
First we are going to clear z in (2):
-5z=25
z=-5
Now let's replace z=-5 in (1):
x+y+2z=-7
x+y+2(-5)=-7
x+y-10=-7 (4)
3x-3y-6z=3
3x-3y-6(-5)=3
3x-3y+30=3 (5)
Now let's clear x in (4):
x+y-10=-7
x=-y+3
Let's replace x=-y+3 in (5):
3x-3y+30=3
3(-y+3)-3y+30=3
-6y+39=3
Now, let's clear y:
-6y+39=3
y=(3-39)/-6
y=-36/-6
y=6
And finally we are going to replace y=6 in x=-y+3
x=-y+3
x=-6+3
x=-3
Finally we obtain that the solution of the system is x=-3, y=6 and z=-5.